STRATEGI KOMUNIKASI FKUB DALAM MEMELIHARA KERUKUNAN UMAT BERAGAMA DI PROVINSI BALI - I Wayan Kontiarta; Redi Panuju (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
The consequences of several Bomb incidents that allegedly carried out by terrorists who hide behind certain religions have led to the emergence of mutual prejudices among the people. Especially in the province of Bali who had experienced the tragedy of the explosion Bomb twice from two thousand two to two thousand five. The notion that the atmosphere among religious life is threatened by religious prejudices. Moreover, media coverage tends to frame the events of terror is always done by hard-line Islamic groups, it is possible that people at the lower level generalize all Muslims tend to be radical. One institution that seeks communication between religious communities is the Forum Kerukunan Umat Beragama (FKUB), whose existence in the province of Bali is very strategic. This article reviews the communication strategies undertaken by FKUB. The research method used is field research by interviewing FKUB figures as key informants. As a result FKUB's strategy contributes to maintaining community harmony, so that at the grassroots level Balinese people remain harmonious.Keywords: Harmony, Communication Strategy, Audience, Local Media, Indigenous Leaders Akibat dari beberapa peristiwa ledakan Bom yang diduga dilakukan oleh teroris yang berlindung di balik agama tertentu telah menyebabkan munculnya saling prasangka di antara umat. Apalagi di Provinsi Bali yang pernah mengalami tragedi ledakan Bom dua kali dari tahun dua ribu dua hingga dua ribu lima. Dugaan bahwa suasana di antara kehidupan umat beragama terancam oleh prasangka agama. Apalagi pemberitaan media cenderung membingkai peristiwa terror selalu dilakukan oleh kelompok Islam berhaluan keras, sangat mungkin masyarakat di tingkat bawah menggeneralisir semua umat Islam cenderung radikal. Salah lembaga yang mengupayakan komunikasi antar umat beragama adalah Forum Kerukunan Umat Beragama (FKUB), yang keberadaannya di Provinsi Bali sangat strategis. Artikel ini meninjau strategi komunikasi yang dilakukan oleh FKUB. Metode penelitian yang digunakan adalah riset lapangan dengan mewawancarai tokoh FKUB sebagai informan kuncu. Hasilnya strategi FKUB memberikan kontribusi dalam memelihara kerukunan umat, sehingga di level akar rumput masyarakat Bali tetap harmonis.Kata Kunci : Kerukunan, Strategi Komunikasi, Khalayak, Media lokal, Tokoh Adat